The Extent to which the 21st Century Skills are Included in the Science Textbook of the Third Grade in Jordan - Abdullah , Hana Najim; Ayaserh , Ahmed Hassan (Dirasat: Educational Sciences, 2023)
Objectives: The study aims to reveal the extent of including 21st century skills in the science textbook for the third grade in Jordan. Methods: The descriptive analytical method was adopted, and a content analysis tool has been designed. It consisted of (47) items that symbolized 21st century skills and represented learning and innovation skills, IT literacy skills, and career and life skills. The analysis tool was applied to the first and second parts of the science textbook. The inclusion of 21st century skills was rated as very high (91%-100%), high (71%-90%), medium (51%-70%), low (31%-50%), and very low (30%- 0%). Results: The results showed that learning and innovation skills had the highest percentage among the 21st century skills in the science textbook for the third grade, as the percentage was (48.3%) and the level of inclusion was low. On the other hand, career and life skills were in the second rank, and their percentage was (14.5%), with a very low inclusion level, while IT and media literacy skills had the lowest percentage (1.9%), and the level of inclusion is very low. Conclusions: This study concluded that 21st century skills in general were at a low level. The study recommended designing development and enrichment activities for the skills of the 21st century, by providing the textbook with activities and academic tasks that take these skills into account.